Power through Translanguaging in Writing Class Discourse: An Indonesian Case Study - Angga Maulana; Wawan Gunawan; Mahardhika Zifana (LPPM Universitas Advent Indonesia, 2025)
This study looks at how power is established when translanguaging occurs in writing class discourse using English as the language of instruction. It is a qualitative research method using a case study methodology. Data collection methods included semi-structured interviews with class lecturers, focus groups with nine students, and classroom observations. Fairclough's (2001) notions of